2016
DOI: 10.3174/ajnr.a4851
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Changes in Anisotropy Are Associated with Outcomes in Mild Traumatic Brain Injury

Abstract: Background and Purpose This prospective longitudinal study identifies early diffusion tensor imaging biomarkers of mild traumatic brain injury that significantly relate to outcomes at 1 year following injury. Materials and Methods DTI was performed on 39 mild traumatic brain injury subjects within 16 days of injury and 40 controls; 26 mild traumatic brain injury subjects returned for follow-up at 1 year. We identified subject-specific regions of abnormally high and low fractional anisotropy, and calculated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 55 publications
3
14
1
Order By: Relevance
“…FA also increases in response to motor training of healthy adults, which suggests that it may be a manifestation of neuroplasticity (38). In addition, higher FA was recently reported as a predictor of better long-term outcome after recognized concussion, suggesting it may be indicative of compensatory change (39). In our study, participants had been exposed to years of repetitive subconcussive heading and, in some cases, periodic impacts of greater severity (ie, recognized concussion).…”
Section: Discussionsupporting
confidence: 54%
“…FA also increases in response to motor training of healthy adults, which suggests that it may be a manifestation of neuroplasticity (38). In addition, higher FA was recently reported as a predictor of better long-term outcome after recognized concussion, suggesting it may be indicative of compensatory change (39). In our study, participants had been exposed to years of repetitive subconcussive heading and, in some cases, periodic impacts of greater severity (ie, recognized concussion).…”
Section: Discussionsupporting
confidence: 54%
“…Substantial evidence by both research previously discussed and the current preliminary study supports the validity and importance of an individualized longitudinal approach with baseline measurements to manage concussion (Strauss et al, ). Despite the low subject number in our current study, the DTI data show promise in providing a sensitive method to temporally monitor brain regions which are vulnerable to concussive injury and to assess each athlete's individual path to recovery.…”
Section: Discussionsupporting
confidence: 70%
“…Using a baseline DTI scan greatly enhances detection of the ef- With these data from baseline, 2-day, 2-week, and 2-month scans, the current study was thus able to elucidate prefrontal WM as a brain region that exhibits pronounced increased diffusivity with prolonged variable recovery following concussion in athletes A recent longitudinal mTBI study that also utilized an individualized approach reported similar increases in RD and MD that additionally correlated with worse memory performance and worse somatic autonomy (Strauss et al, 2016). Interestingly, the authors suggest that increased RD may serve as a good early predictor of long-lasting dysfunction (Strauss et al, 2016). Even though post-injury FA abnormalities were also reported, all of the post-injury time points in the current study displayed insignificant FA results.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A voxel-wise analysis of covariance (VANCOVA) was performed to identify subjectspecific abnormalities in DTI parameters including Fractional Anisotropy (FA), Radial Diffusivity (RD), Axial Diffusivity (AD), and Mean Diffusivity (MD). As previously described (26,27), this is a method that permits us to identify clusters (e.g., a grouping of voxels) of DTI abnormalities by comparing each individual subject to a group of normative controls. In the present study, DTI parameter image volumes from each soccer player were compared to those of 110 healthy controls to identify subjectspecific abnormalities in DTI parameters.…”
Section: Diffusion Tensor Imaging (Dti)mentioning
confidence: 99%